Gate oxide degradation of SiC MOSFET under short-circuit aging tests. (September 2016) - Mbarek, S.; Fouquet, F.; Dherbecourt, P.; Masmoudi, M.; Latry, O.
Abstract: SiC MOSFETs reliability issues remain a challenge that requires further investigation. In this article, a short-circuit aging test was developed to characterize the electrical parameter evolution. The threshold voltage and gate drain capacitance seem to be relevant degradation indicators. These two parameters indicate a gate oxide degradation. Electron trapping in the oxide layer could be the mechanism behind this deterioration. Graphical abstract: Highlights: A new approach for short-circuit aging of SiC MOSFET is proposed at low drain voltage and long pulse durations. The threshold voltage shift is due to oxide charge trapping and interface charges. The threshold voltage shift is proportional to the reverse capacitance (measured at VGS = 0V) shift. The threshold voltage and gate capacitance are valuable health indicators. PBTI can be the failure mechanism behind the devices degradation.